Coerced: work under threat of punishment - Hatton, Erin Elisabeth (University of California Press, 2020)
Introduction -- "Wicked" and "blessed" : cultural narratives of coerced labor -- "Either you do it or you're going to the box" : coercion and compliance -- "They talk to you in any kind of way" : subjugation, vulnerability, and the body -- "Stay out they way" : agency and resistance -- "I'm getting Ethiopia pay for my work" : hegemony and counter-hegemony -- Conclusion -- Appendix I : the story of this book -- Appendix II : People qua data.